2008
DOI: 10.1016/j.mcn.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive, agonist-accelerated, recycling and lysosomal degradation of GABAB receptors in cortical neurons

Abstract: Endocytosis is considered as an important mechanism for regulating cell surface numbers and thereby signaling strength of G protein-coupled receptors. Currently, little is known about the endocytotic pathways of GABA B receptors in neurons. Here we report that GABA B receptors are constitutively internalized presumably via clathrin-dependent endocytosis in cultured cortical neurons. Colocalization of GABA B receptors with endosomal marker proteins indicated sorting of GABA B receptors from early endosomes to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 22 publications
6
68
0
Order By: Relevance
“…2C). Therefore, after being internalized, GABA B receptors are recruited to early endosomes, from where they are either recycled via recycling endosomes to be reinserted into the plasma membrane or are degraded in the lysosomes via the late endosomes, consistent with previous findings (14,15,27,28). The process of recycling would account for the plateau phase in the time profiles of surface fluorescence (Fig.…”
Section: Trafficking Of Gaba B Receptor and R2supporting
confidence: 88%
See 1 more Smart Citation
“…2C). Therefore, after being internalized, GABA B receptors are recruited to early endosomes, from where they are either recycled via recycling endosomes to be reinserted into the plasma membrane or are degraded in the lysosomes via the late endosomes, consistent with previous findings (14,15,27,28). The process of recycling would account for the plateau phase in the time profiles of surface fluorescence (Fig.…”
Section: Trafficking Of Gaba B Receptor and R2supporting
confidence: 88%
“…Previous studies have proposed that GABA B receptors are very stable on the cell surface (10,11), whereas more recent reports have indicated that GABA B receptors are mobile, being rapidly and constitutively internalized in the absence of agonist in both heterologous expression systems and neurons (12)(13)(14)(15). To date, most studies addressing GABA B receptor trafficking necessarily utilized fixed cells in conjunction with surface receptor biotinylation or C-terminal antibody labeling to monitor receptor subunit mobility.…”
mentioning
confidence: 99%
“…1C). Agonists accelerate basal endocytosis of GABA B receptors (25). Antagonizing GABA B receptor activity with CGP54626A (2 μM for 10 min) did not attenuate NMDAmediated removal of surface GABA B1b protein (NMDA + CGP54626A: 60.2 ± 9.6% of control, n = 10, P < 0.05; Fig.…”
Section: Nmda Receptorsmentioning
confidence: 85%
“…S2B). Following glutamate or NMDA treatment, a fraction of internalized GABA B1b protein segregated into structures devoid of Rab11-eGFP, possibly indicating GABA B1b protein targeted for degradation (24,25). Preincubation of neurons with dynasore (80 μM for 15 min), a cell-permeable inhibitor of dynamin-dependent endocytosis (26), interfered with the NMDA-mediated removal of surface GABA B1b protein (NMDA: 58.8 ± 5.4% of control, n = 8, P < 0.05; NMDA + dynasore: 105 ± 10% of control, n = 10, P > 0.05; dynasore: 98.4 ± 9.0% of control, n = 9, P > 0.05; Fig.…”
Section: Nmda Receptorsmentioning
confidence: 99%
“…Although GABA B receptor is known to undergo basal endocytosis, it remains controversial whether agonist stimulation facilitates receptor internalization Grampp et al, 2008Grampp et al, , 2007. Thus, some studies attribute the cell surface stability of GABA B receptor to a lack of agonist-induced internalization Perroy et al, 2003), whereas others suggest that this might be due to re-insertion of the receptor into the plasma membrane by an unknown mechanism (Grampp et al, 2008(Grampp et al, , 2007Wilkins et al, 2008).…”
Section: Introductionmentioning
confidence: 99%